Biofilms formation and prevention on urinary catheters: a bibliometric analysis (Bioscience Journal, 2020)
To map the scientific production about biofilms formation and prevention on urinary catheters. It is a bibliometric, exploratory, and descriptive research performed in Web of Science™, in three stages, and utilizing HistCite™ software. In this regard, descriptors “Biofilm*” AND “Urinary Catheter*” were utilized within the period between 1945 and 2016. A total of 329 articles about biofilm on urinary catheter were found from 1985 to 2016. These articles were written by 1,262 authors from 452 institutions located in 50 countries. The relation among the 15 selected articles, the most impacting ones, evidences the existence of experimental researches; most of them was in vitro. The control of biofilm formation on urinary catheters remains as a major challenge in the health area, because new ways are necessary to improve the prevention and minimization of this phenomenon.